The Use of Public Relation in the Community Service Campaign “BAKDES” in the English Study Program Association Organization (HAMLET) Universitas Trunojoyo Madura - Fitriyah Fitriyah; Eka Susylowati (Journal of Social, Culture, and Language, 2025)
This study aims to analyze the PR strategy used by HAMLET, assess its effectiveness in achieving the campaign objectives, and identify important lessons learned for future community engagement initiatives. This research uses a qualitative approach with a case study design to investigate the use of Public Relations (PR) strategies in the BAKDES campaign conducted by HAMLET, the Student Association of the English Education Study Program at Trunojoyo Madura University (UTM). This case study has demonstrated the crucial role of strategic public relations (PR) in maximizing the impact and sustainability of community service projects. HAMLET's successful implementation of the BAKDES campaign highlights the value of utilizing a multi-pronged PR strategy, building strong relationships with stakeholders, and crafting a compelling narrative.